Evidence suggesting that a novel guanine nucleotide regulatory protein couples receptors to phospholipase C in exocrine pancreas. - Merritt, J E (1986)
The initial response of many cells to 'Ca2+-mobilizing' agonists is phospholipase C-mediated hydrolysis of phosphatidylinositol bisphosphate to inositol trisphosphate (IP3) and diacylglycerol. It has been suggested, by analogy with receptor regulation of adenylate cyclase, that 'Ca2+-mobilizing' receptors may interact with a guanine nucleotide-binding protein (G protein) to regulate phospholipase C activity. Here we report increased accumulation of IP3 in response to caerulein or carbachol in electrically permeabilized rat pancreatic acinar cells. The stable analogues of GTP (guanosine 5'-[gamma-thio]trisphosphate and guanosine 5'-[beta, gamma-imido]triphosphate) stimulate IP3 accumulation and potentiate the effects of caerulein and carbachol. This synergism demonstrates an interaction between receptors, a G protein and phospholipase C. These responses are unaffected by pretreatment of the cells with pertussis or cholera toxins under conditions that produce substantial covalent modification of Gi and Gs, the proteins that couple receptors to adenylate cyclase. We therefore conclude that the G protein that couples receptors to phospholipase C in exocrine pancreas is probably neither Gi nor Gs; instead, we propose that a different G protein mediates this effect.